(untitled) (ELECTRICAL MACHINES, MATERIALS AND DRIVES — PRESENT AND TRENDS, 2025)
This presentation concerns developing and testing an experimental model of a frequency converter based on IGBT transistors, controlled by a microcontroller, used to power a 5-phase asynchronous machine with a nominal power of 5 kW. The hardware implementation and the main elements of the control and diagnostic software, developed to ensure the control of a general-purpose converter, which can be used to drive a light electric vehicle powered by batteries, are presented. The measurements also include the behavior of the drive when a phase separation fault occurs. DOI: https://doi.org/10.36801/apme.2024.1.9